The development of an interactive multimedia software program in library and information science - Cabbab, Johann Frederick A. 1972-
A total of 78 (22 percent) students of the University of the Philippines Institute of Library Science of the total student population of 353 were chosen as respondents for this study to test the interactive multimedia software program developed based on the introductory courses in librarianship. Content data were collected, the program was designed and it was then developed using Object Pascal and HTML 3.3. The software used were Delphi 3 and Microsoft Frontpage Express.